Stereochemistry of ring-opening/cross metathesis reactions of exo- and endo-7-oxabicyclo[2.2.1]hept-5-ene-2-carbonitriles with allyl alcohol and allyl acetate - Wałejko, Piotr; Dąbrowski, Michał; Szczepaniak, Lech; Morzycki, Jacek W.; Witkowski, Stanisław (Beilstein Journal of Organic Chemistry, 2015)
The ROCM reactions of exo- and endo-2-cyano-7-oxanorbornenes with allyl alcohol or allyl acetate promoted by different ruthenium alkylidene catalysts were studied. The stereochemical outcome of the reactions was established. The issues concerning chemo- (ROCM vs ROMP), regio- (1-2- vs 1-3-product formation), and stereo- (E/Z isomerism) selectivity of reactions under various conditions are discussed. Surprisingly good yields of the ROCM products were obtained under neat conditions.
Keywords: Grubbs’ catalysts; metathesis; ROCM; ROMP; Z-selectivity

(untitled) - Wolfe, J. P.; Hay, M. B. (Tetrahedron, 2007)

(untitled) - Faul, M. M.; Huff, B. E. (Chem. Rev., 2000)

(untitled) - Bermejo, A.; Figadère, B.; Zafra-Polo, M.-C.; Barrachina, I.; Estornell, E.; Cortes, D. (Nat. Prod. Rep., 2005)

(untitled) - Ramu, E.; Bhaskar, G.; Rao, B. V.; Ramanjaneyulu, G. S. (Tetrahedron Lett., 2006)

(untitled) - Saleem, M.; Kim, H. J.; Ali, M. S.; Lee, Y. S. (Nat. Prod. Rep., 2005)

(untitled) - Hirao, H.; Yamauchi, S.; Ishibashi, F.; Ishibashi, F. (Biosci., Biotechnol., Biochem., 2007)

(untitled) - Fessel, J. P.; Porter, N. A.; Moore, K. P.; Sheller, J. R.; Roberts, L. J. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Song, W.-L.; Lawson, J. A.; Reilly, D.; Rokach, J.; Chang, C.-T.; Giasson, B.; FitzGerald, G. A. (J. Biol. Chem., 2008)

(untitled) - Kang, E. J.; Lee, E. (Chem. Rev., 2005)

(untitled) - Oikawa, M.; Ikoma, M.; Sasaki, M.; Gill, M. B.; Swanson, G. T.; Shimamoto, K.; Sakai, R. (Eur. J. Org. Chem., 2009)

(untitled) - Benjamin, N. M.; Martin, S. F. (Org. Lett., 2011)

(untitled) - Akiyama, K.; Yamauchi, S.; Nakato, T.; Maruyama, M.; Sugahara, T.; Kishida, T. A. (Biosci., Biotechnol., Biochem., 2007)

(untitled) - Kress, S.; Blechert, S. (Chem. Soc. Rev., 2012)

(untitled) - Holub, N.; Blechert, S. (Chem. – Asian J., 2007)

(untitled) - Connon, S. J.; Blechert, S. (Angew. Chem., Int. Ed., 2003)

(untitled) - Aljarilla, A.; Murcia, M. C.; Csákÿ, A. G.; Plumet, J. (Eur. J. Org. Chem., 2009)

(untitled) - Arjona, O.; Csákÿ, A. G.; Plumet, J. (Eur. J. Org. Chem., 2003)

(untitled) - Schneider, M. F.; Blechert, S. (Angew. Chem., Int. Ed. Engl., 1996)

(untitled) - Schneider, M. F.; Lucas, N.; Velder, J.; Blechert, S. (Angew. Chem., Int. Ed. Engl., 1997)

(untitled) - Arjona, O.; Csákÿ, A. G.; Murcia, M. C.; Plumet, J. (J. Org. Chem., 1999)

(untitled) - Liu, Z.; Rainier, J. D. (Org. Lett., 2005)

(untitled) - Voigtritter, K.; Ghorai, S.; Lipshutz, B. H. (J. Org. Chem., 2011)

(untitled) - Venkata, C.; Forster, M. J.; Howe, P. W. A.; Steinbeck, C. (PLoS One, 2014)

(untitled) - Herzig, J.; Nudelman, A. (Carbohydr. Res., 1986)

(untitled) - van Den Dool, H.; Kratz, P. D. (J. Chromatogr. A, 1963)

(untitled) - Holtsclaw, J.; Koreeda, M. (Org. Lett., 2004)

(untitled) - Fortman, G. C.; Nolan, S. P. (Chem. Soc. Rev., 2011)

(untitled) - Brion, F. (Tetrahedron Lett., 1982)

(untitled) - Vieira, E.; Vogel, P. (Helv. Chim. Acta, 1983)

(untitled) - Chau, C. W.; Fawcett, A. H.; Mulemwa, J. N.; Tan, C. E. (Polymer, 1985)

(untitled) - Morton, C. J. H.; Gilmour, R.; Smith, D. M.; Lightfoot, P.; Slawin, A. M. Z.; MacLean, E. J. (Tetrahedron, 2002)